Overcome the Habit of Procrastination with the Role of Self-Control in Optimizing Student Performance in Organizations - Erina Putri, Amanda (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Students involved in school organizations usually tend to procrastinate because they have to carry out their tasks. The purpose of this research is to examine the influence of self-control on procrastination among high school student council members. Data collection used a quantitative method involving 115 students who participated in the student council using purposive sampling technique. The measurement tool in this study is procrastination, which consists of engaging in more enjoyable activities, delaying the start or completion of tasks, the time gap between plans and actual performance, and delays in task completion. Meanwhile, self-control consists of cognitive control, decision control, and behavioral control. The data analysis technique is simple regression. The analysis results show a significance value of 0.004 with an F value of 8.554 and an R square value of 0.070, while the rest is influenced by other factors outside the research, namely self-efficacy, self-regulation, self-confidence, and parenting style. This means that the higher the self-control, the lower the academic procrastination, and the lower the self-control, the higher the academic procrastination.Siswa yang terlibat dalam organisasi sekolah biasanya cenderung melakukan prokrastinasi karena harus menjalankan tugasnya. Tujuan penelitian ini untuk menguji pengaruh kontrol diri terhadap prokrastinasi pada anggota OSIS sekolah menengah atas. Pengumpulan data menggunakan metode kuantitatif berjumlah 115 siswa yang mengikuti OSIS menggunakan teknik purposive sampling. Alat ukur dalam penelitian ini yaitu prokrastinasi terdiri dari melakukan aktivitas yang lebih menyenangkan, penundaan untuk memulai maupun menyelesaikan tugas, kesenjangan waktu antara rencana dan kinerja aktual, dan keterlambatan dalam mengerjakan tugas. Sedangkan kontrol diri terdiri dari kontrol kognitif, kontrol keputusan, dan kontrol perilaku. Teknik analisis data adalah teknik regresi sederhana. Hasil analisis menunjukkan nilai signifikansi sebesar 0,004 dengan nilai F sebesar 8,554 dan nilai R square sebesar 0,070 lalu sisanya di pengaruhi oleh faktor lain di luar penelitian yaitu efikasi diri, regulasi diri, kepercayaan diri, pola asuh orangtua. Hal ini bermakna bahwa semakin tinggi kontrol diri maka semakin rendah prokrastinasi akademik, dan semakin rendah kontrol diri maka semakin tinggi prokrastinasi akademik.